A Relation between π Generalized Pre Connectedness and π Generalized Supra Connectedness In Intuitionistic Fuzzy Topological Space - Omer S Mustfa (Tikrit Journal of Pure Science)
The aim of this paper is to give the concepts of intuitionistic fuzzy  generalized pre connectedness with study its properties. Finally we study the relation between intuitionistic fuzzy  generalized pre connectedness and intuitionistic fuzzy  generalized supra connectedness in intuitionistic fuzzy topological space .